Renewable energy: wind lawn mower / Abdullah Munzir Mohd Rashdi, Ahmad Wafi Mohd Suhaimi and Ahmad Fauzan Hudari - Mohd Rashdi, Abdullah Munzir; Mohd Suhaimi, Ahmad Wafi; Hudari, Ahmad Fauzan (2015)
Wind energy is one of the renewable energy. It is using wind generator. Winds that blow through the blade which attach at the generator also rotate the rotor inside the generator. When the rotor spins, in the conduct, it will produce electric field and magnet produce magnetic field. Next, when there is magnetic field exist, magnetic flux occur. In order to cut the grass using wind energy, we have designed and implemented an electronic circuit plus we control the speed of DC motor. Our main device is generator that functioning as a generative the energy to the 12V led acid battery.